ADAM17 knockdown mitigates while ADAM17 overexpression aggravates cardiac fibrosis and dysfunction via regulating ACE2 shedding and myofibroblast transformation - Cheng, Jing; Xue, Fei; Cheng, Cheng; Sui, Wenhai; Zhang, Meng; Qiao, Lei; Ma, Jing; Ji, Xiaoping; Chen, Wenqiang; Yu, Xiao; Xi, Bo; Xu, Feng; et al. (Frontiers in Pharmacology, 2022)
A disintegrin and metalloprotease domain family protein 17 (ADAM17) is a new member of renin-angiotensin system (RAS) but its role in the pathogenesis of diabetic cardiomyopathy (DCM) is obscure. To test the hypothesis that ADAM17 knockdown mitigates while ADAM17 overexpression aggravates cardiac fibrosis via regulating ACE2 shedding and myofibroblast transformation in diabetic mice, ADAM17 gene was knocked down and overexpressed by means of adenovirus-mediated short-hairpin RNA (shRNA) and adenovirus vector carrying ADAM17 cDNA, respectively, in a mouse model of DCM. Two-dimensional and Doppler echocardiography, histopathology and immunohistochemistry were performed in all mice and in vitro experiments conducted in primary cardiofibroblasts. The results showed that ADAM17 knockdown ameliorated while ADAM17 overexpression worsened cardiac dysfunction and cardiac fibrosis in diabetic mice. In addition, ADAM17 knockdown increased ACE2 while reduced AT1R expression in diabetic hearts. Mechanistically, ADAM17 knockdown decreased while ADAM17 overexpression increased cardiac fibroblast-to-myofibroblast transformation through regulation of TGF-β1/Smad3 signaling pathway. In conclusion, ADAM17 knockdown attenuates while ADAM17 overexpression aggravates cardiac fibrosis via regulating ACE2 shedding and myofibroblast transformation through TGF-β1/Smad3 signaling pathway in diabetic mice. Targeting ADAM17 may provide a promising approach to the prevention and treatment of cardiac fibrosis in DCM.